The environmental crisis-- opposing viewpoints - Bernards, Neal, 1963- (San Diego, CA : Greenhaven Press, 1991)
Presents opposing views on questions of environmental protection and damage resulting from air and water pollution, toxic wastes, pesticides, and the ever-growing tide of refuse.
Is there an environmental crisis? -- How should pesticides be handled? -- How can the garbage problem be reduced? -- How should America dispose of toxic waste? -- How serious is air and water pollution? -- How can the environment be protected?
Includes bibliographical references (p. 282-283) and index.
School Library Journal.
Wilson's Junior High School.
Wilson's Senior High School.
10-12
Young Adult
Keywords: Environmental policy -- United States; Environmental protection -- United States; Environmental policy; Environmental protection